The Relationship between Speaking and Writing in Descriptive Discourse in a Moroccan University EFL Context - Akki, Fouad; Larouz, Mohammed (International Journal of Linguistics and Translation Studies, 2021)
The present paper aims at investigating the relationship between speaking and writing in descriptive discourse among Moroccan university EFL students within the department of English Studies at Moulay Ismail University, Meknes, Morocco. To attain this end, 80 undergraduate semester six students studying English as a foreign language were randomly selected to participate in the current study. Subsequently, speaking and writing proficiency tests were administered to the participants to measure their descriptive abilities in speaking and writing. The data were analyzed by carrying out correlation and regression analysis in SPSS. The results reveal that there is a strong positive and statistically significant correlation between speaking and writing in descriptive discourse, r = .61. Descriptive speaking can predict 37 percent of EFL students’ descriptive writing (R2 =.37). The study ends with implications for teachers, syllabus designers, and the department of English studies.